العزو السببي للنجاح والفشل الأكاديمي بإختلاف الجنس والتخصص الأكاديمي لدى طلبة الجامعة - مراح، مليكة (جامعة الوادي university of Eloued, 2019)
Abstract : The study aimed to measure the differences in causal attribution patterns of success and academic failure among university students according to academic specialization and gender. The study hypotheses: - There are differences in statistical significance in the patterns of causation of success and academic failure by sex and academic specialization. - There are differences of statistical significance in the patterns of causation of success and academic failure according to gender. - There are differences of statistical significance in the patterns of causality of success and academic failure according to different academic specialization. The study also relied on the descriptive method in verifying the hypotheses. The comparative method was used in the treatment of hypotheses. The sample was randomly selected from first year master students of the Faculty of Social and Human Sciences as well as the Faculty of Nature and Life Sciences for the academic year (2018-2019). The study relied on the measure of attribution patterns for success and academic failure. The results were as follows: - There are no statistically significant differences in the patterns of causality of success and academic failure according to gender. - There are differences of statistical significance in the patterns of lack of causality of success and academic failure according to different academic specialization - The results were discussed in the light of some previous studies. - The study concluded with some suggestions that would open the horizons for new scientific researches. Mots clés:Causality, success, failure الملخص : هدفت الدراسة إلى قياس الفروق في أنماط العزو السببي للنجاح والفشل الأكاديمي لدى طلبة الجامعة باختلاف التخصص الأكاديمي والجنس. وقد طرحت الدراسة الفرضيات التالية: 1-توجد فروق ذات دلالة احصائية في أنماط العوز السببي للنجاح والفشل الأكاديمي باختلاف الجنس. 2-توجد فروق ذات دلالة احصائية في أنماط العوز السببي للنجاح والفشل الأكاديمي باختلاف التخصص الأكاديمي. كما اعتمدت الدراسة على المنهج الوصفي في التحقق من الفرضيات؛ حيث تم استخدام الأسلوب المقارن في فرضيات الدراسة أما العينة فقد اختيرت بطريقة عشوائية من طلبة أولى ماستر لكلية العلوم الاجتماعية والانسانية؛ وكذا كلية علوم الطبيعة والحياة،للسنة الجامعية( 2018-2019)، هذا واعتمدت الدراسة على مقياس أنماط العزو السببي للنجاح والفشل الأكاديمي لفيكتوريت، وتم استخدام اختبار (T.test)للتحقق من الفرضية الاولى والثانية؛ وقد كانت النتائج المتوصل إليها كالآتي: 1-لا توجد فروق ذات دلالة احصائية في أنماط العوز السببي للنجاح والفشل الاكاديمي باختلاف الجنس. 2- توجد فروق ذات دلالة احصائية في انماط العوز السببي للنجاح والفشل الاكاديمي باختلاف التخصص الأكاديمي وقد تم تفسير النتائج في ضوء بعض الدراسات السابقة وختمت الدراسة ببعض المقترحات الموجهة إلى المهتمين بالبحث العلمي؛ والتي من شأنها أن تفتح آفاقا لأبحاث علمية جديدة.
دراسة وصفية مقارنة على عينة من طلبة سنة أولى ماستر بجامعة الوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الغزو السببي; invasion causale; causal invasion